An Introduction to Harvest Tags for Marine Recreational Fisheries - Edward Camp; Zachary Siders; Andrew Ropicki; Frank Asche (EDIS, 2023)
Managing recreational fisheries requires balancing sustainability against allowing as much access and harvest as possible. Maintaining sustainability is made harder by discard mortality where any fishing activity, even catch and release, risks fish dying from injuries, predation, or other causes. This is especially a problem for Florida reef fish species that live at depths and habitats where barotrauma increases mortality and depredation by larger fish, sharks, or marine mammals increases it further. Harvest (or trip) tags could reduce overharvest, lower discard mortality, and allow anglers more freedom to choose when to fish. Harvest tags would limit the total fish harvested, but could eliminate one of the least popular current management restrictions, harvest seasons. This publication describes harvest tag approaches, discussing how they are already used in fishing and hunting and describing some of the potential benefits and costs if they were applied in Florida.